2015
DOI: 10.14423/smj.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neighborhood Environments on Health Consciousness, Information Seeking, and Attitudes among US-Born and Non–US-Born Free Clinic Patients

Abstract: Health education programs for free clinic patients should include strategies to increase social cohesion. Health education programs should consider the diverse needs of these individual populations to maximize the effectiveness of the programs for free clinic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Although previous studies have established a positive influence of HC, few explore the relationship between race/ethnicity and HC. Our findings parallel other research that reports higher levels of HC among minority populations, 8,10 particularly among those who strongly identify with their racial/ethnic background. 30 Our results support research linking HC with community participation 14 and extend it to include social support and social network participation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although previous studies have established a positive influence of HC, few explore the relationship between race/ethnicity and HC. Our findings parallel other research that reports higher levels of HC among minority populations, 8,10 particularly among those who strongly identify with their racial/ethnic background. 30 Our results support research linking HC with community participation 14 and extend it to include social support and social network participation.…”
Section: Discussionsupporting
confidence: 89%
“…Although some research indicates that minority communities report higher levels of HC compared to their white counterparts, 8 studies also indicate that minority groups tend to engage in fewer cancer prevention behaviors overall. 8,9 Other studies investigating HC consumers suggest that non-Hispanic whites and non-Hispanic white households are less HC and engage in less health information seeking and scanning than other racial and ethnic groups, 8,10,11 which may be due to greater disease burden among minority groups. 12 Thus, more research is needed to better understand the role of racial and ethnic identity in HC and its relationship with cancer prevention behaviors and disparities.…”
mentioning
confidence: 99%
“…It is interesting to note that US born English speakers (many of whom are white) most frequently neglected their oral health and preventive care, in contrast to a previous study that demonstrated that Hispanics and Asians reported similar frequencies of preventive care to non‐Hispanic whites . Additionally, US born English speaking free clinic patients are less likely to attend a health education class and have lower levels of health consciousness and health information seeking tendencies compared to non‐US born English speaking or Spanish speaking free clinic patients . The low levels of health consciousness amongst US born English speakers may be related to the neglectful oral health behaviors also reported in this population.…”
Section: Discussionmentioning
confidence: 82%
“…Participants were categorized to the following three groups: US born English speakers, non‐US born English speakers, and Spanish speakers. The reasoning for this is because previous studies have suggested that free clinic patients in these groups differ from each other in regards to health‐related behaviors . Participants who took the survey in English were considered English speakers, while those who took the survey in Spanish were considered Spanish speakers.…”
Section: Methodsmentioning
confidence: 99%
“…These barriers include low socioeconomic status, minority race and/or ethnicity, lack of transportation, and low literacy [1]. Addressing disease prevention, management of chronic disease, improving health services, increasing access to primary health care resources, identifying integral community partners, and allowing qualified health professionals to efficiently conduct their jobs can create successful results [2]. Task-based, as a opposed to patient-centered care, involves attitudes lacking compassionate characteristics such as empathy, warmth, sensitivity, and kindness [3].…”
Section: Introductionmentioning
confidence: 99%